Estimating General Equilibrium Trade Policy Effects: GE PPML - James E. Anderson; Mario Larch; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2015)
We develop a simple estimation procedure for general equilibrium (GE) comparative static analysis of gravity models. Non-linear solvers of estimated models are replaced by (constrained) regressions. Applied economists can more readily generate results, with more intuition about the working of the model. We illustrate with a worldwide border removal application using the Poisson Pseudo-Maximum-Likelihood (PPML) estimator in STATA, iterated to deliver conditional and full general equilibrium responses. The method works by fully exploiting the combined properties of structural gravity and PPML. Our procedures readily extend to a wide class of general equilibrium production models.
Keywords: F10; F14; F16; 330; structural gravity; general equilibrium effects; counterfactuals; estimation